Tracing Adolescent Girls' Motivation Longitudinally: From FitClub Participation to Leisure-Time Physical Activity. Issue 5 (October 2019) - Laroche, Julie-Anne; Girard, Stephanie; Lemoyne, Jean
Scientific evidence reveals a significant decline in exercise behaviors during adolescence. Although multiple school-based initiatives have been implemented in Canada, little is known of how these initiatives affect students' motivation for subsequent physical activity (PA). The transcontextual model of motivation offers an interesting approach to assessing the long-term, motivational impact of school-based interventions, and we used this model to study how adolescent girls' need satisfactions, first observed within supervised PA (in the FitSpirit FitClub), correlated with their inclinations toward nonsupervised PA behaviors later. Adolescent girls in this study ( N  = 259; M  = 14.34, SD =  1.49 years) completed a transcontextual model of motivation-based questionnaire regarding their basic psychological needs, motivation, attitudes, subjective norms, perceived behavioral control, intentions, and PA practice during their FitSpirit club participation. Three weeks after this participation, they reported their PA levels again. The girls' basic psychological needs predicted their autonomous motivation in the FitClub. Their autonomous motivation predicted subjective norms and perceived behavioral control; these factors then determined their intentions to be physically active, and their PA intentions predicted their actual PA behavior during personal (leisure) time three weeks later. Two indirect paths were statistically significant for predicting PA intentions, and three indirect paths were significant for predicting leisure-time PA. Activity motivation, first developed within a supervised context, can increase subsequent leisure-time PA.